Rigid helical-like assemblies from a self-aggregating tripeptide - Bera, Santu (Nat Mater, 2019)
The structural versatility, biocompatibility and dynamic range of the mechanical properties of protein materials have been explored in functional biomaterials for a wide array of biotechnology applications. Typically, such materials are made from self-assembled peptides with a predominant β-sheet structure, a common structural motif in silk and amyloid fibrils. However, collagen, the most abundant protein in mammals, is based on a helical arrangement. Here we show that Pro-Phe-Phe, the most aggregation-prone tripeptide of natural amino acids, assembles into a helical-like sheet that is stabilized by the dry hydrophobic interfaces of Phe residues. This architecture resembles that of the functional PSMα3 amyloid, highlighting the role of dry helical interfaces as a core structural motif in amyloids. Proline replacement by hydroxyproline, a major constituent of collagen, generates minimal helical-like assemblies with enhanced mechanical rigidity. These results establish a framework for designing functional biomaterials based on ultrashort helical protein elements.